ROMANIAN FREE CHOICE FREE RELATIVES: A COMPARISON WITH SUBTRIGGED FREE CHOICE SENTENCES (Bucharest Working Papers in Linguistics, 2024)
The present study focuses on the semantic and pragmatic properties of Romanian free choice free relatives (FC FRs ), with the following con clusions: the quantificational force of FC FRs in Romanian is definite ; t he apparent universal force is the outcome of an evaluation constraint of the fre e choice particle: t he syntax of FC FRs in Romanian is the same as that of E nglish ever FRs; Romanian FC FRs most closely resemble the semantics and pragmatics of subtrigged free choice determiners. T he distribution and interpretation of Romanian FC FRs is assumed to be of three main kinds: auto licensing, on a par with subtrigging; licensing by a modal o perator in a non generic/non habitual context on a par with FCI determiners li censed in the same environments ; licensing by a generic or habitual operator (also on a par with determiner FCIs). As shown in Panaitescu (2022), the three types of contexts diff er in the type of universality they display: serial universality, parallel universality (the apparent existential reading) and atemporal universality.